2011
DOI: 10.1172/jci45416
|View full text |Cite
|
Sign up to set email alerts
|

Protective T cell immunity in mice following protein-TLR7/8 agonist-conjugate immunization requires aggregation, type I IFN, and multiple DC subsets

Abstract: The success of a non-live vaccine requires improved formulation and adjuvant selection to generate robust T cell immunity following immunization. Here, using protein linked to a TLR7/8 agonist (conjugate vaccine), we investigated the functional properties of vaccine formulation, the cytokines, and the DC subsets required to induce protective multifunctional T cell immunity in vivo. The conjugate vaccine required aggregation of the protein to elicit potent Th1 CD4 + and CD8 + T cell responses. Remarkably, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
134
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 114 publications
(135 reference statements)
11
134
0
Order By: Relevance
“…This was expected as we have previously shown that subvisible‐sized aggregates of scFv promote a Th1‐skewed response 22. It is possible that the Th1 skewing is an effect of differential antigen processing and presentation, and this effect is also consistent with the hypothesis that the repetitive epitopes formed by aggregation can mimic characteristics of microbes and viruses 28. The anti‐scFv response was higher still with the addition of DnaK, but in aggregated preparations only, where an increase in anti‐scFv IgG and IgG2a was observed.…”
Section: Discussionsupporting
confidence: 85%
“…This was expected as we have previously shown that subvisible‐sized aggregates of scFv promote a Th1‐skewed response 22. It is possible that the Th1 skewing is an effect of differential antigen processing and presentation, and this effect is also consistent with the hypothesis that the repetitive epitopes formed by aggregation can mimic characteristics of microbes and viruses 28. The anti‐scFv response was higher still with the addition of DnaK, but in aggregated preparations only, where an increase in anti‐scFv IgG and IgG2a was observed.…”
Section: Discussionsupporting
confidence: 85%
“…28 Purified detoxified nDer p 2 was chosen as a broadly recognized T H 2-inducing HDM allergen. 29 Modified 8-OH adenines are small polar molecules able to gain the endosomal compartment, 15 which might undergo alteration in transmembrane permeability when conjugated. Actually, our adduct still triggered human and murine TLR7, with no activation of other nucleic acid-recognizing receptors (TLR3, TLR8, or TLR9) or cytosolic innate sensors differently from other immunomodulatory heterocycles.…”
Section: Discussionmentioning
confidence: 99%
“…14 By using the same conjugation procedure, it was also observed that vaccination with an ovalbumin/3M042-coupled compound resulted in an IL-12p40-and type I interferondependent strong CD4 1 and CD8 1 T H 1 immunity, promoting antigen uptake by several resident and migratory DC subsets. 15 We have previously shown that the mixture of an antigen (or a hapten) with 2,9-substituted 8-hydroxy adenines deeply influenced the phenotype of antigen-specific effectors both in human subjects and mice. 16,17 Taking advantage of a coupling technique using mild nondenaturing conditions and untouched proteins, we show here that a conjugated compound between 4-(6-amino-9-benzyl-8-hydroxy-9H-purin-2-ylsulfanyl)-butyric acid succinimidyl ester (an 8-OH modified adenine; SA-26E) and the purified natural Dermatophagoides pteronyssinus group 2 allergen from house dust mite (HDM) is able to redirect allergen-specific T H 2 responses in human subjects in vitro and to promote a T H 1 profile in a murine model of allergic sensitization in vivo through TLR7 triggering without harmful effects, such as induction of autoantibodies or overt autoimmunity.…”
mentioning
confidence: 99%
“…He reported on his recent discovery that a conjugate vaccine comprising aggregated protein linked to a TLR7/8 agonist caused the recruitment of migratory DCs into local draining lymph nodes that greatly enhanced antigen uptake by both resident and migratory DCs and led to broadbased T-cell-mediated immunity composed of multifunctional CD4 þ and CD8 þ T-cell responses. 3 The application of this approach was demonstrated in a mouse model Listeria monocytogenes infection requiring a strong Th1-mediated protective immune response, and broader applications were proposed in malaria with a live-attenuated malaria vaccine designed to protect against liver-stage disease via CD8 þ T-cell-mediated immunity.…”
Section: Harnessing T Cells: a Dance With Dendritic Cellsmentioning
confidence: 99%